PENGELOLAAN BANTUAN EKONOMI BAGI ANAK YATIM MELALUI PROGRAM KANTOR URUSAN AGAMA DI KECAMATAN JONGKONG KABUPATEN KAPUAS HULU - Arif Fahrudin; Vera Susanti (Adisam Publisher, 2023)
This research is motivated by realizing ourselves as caliphs of Allah, in fact there is not a single human being in this world who does not have a